The Association of Body Mass Index, Physical Activity and Hypertension in Indonesia - Hodimatum Mahiroh; Erni Astutik; Rochmad Ardiansyah Pratama (Universitas Airlangga, 2019)
Introduction: Hypertension can cause cardiovascular disease, and it is still a serious global problem. The Prevalence of hypertension has increased every year. Some of the factors associated with hypertension are obesity and physical activity. The prevalence of obesity has increased every year, and many people have lower levels of physical activity. This study aims to analyse the correlation between Body Mass Index (BMI), physical activity and hypertension in Indonesia. Methods: This study used a cross-sectional study design using secondary data from the Indonesia Family Life Survey 5 (IFLS5) conducted in 2014 - 2015. The sample consisted of individuals in the households interviewed and 26,472 Respondents fulfilled the criteria. The data were analysed using multivariate logistic regression. Results: The results showed that most of the respondents were of productive age. More than half of the respondents were female (52.05%). The respondents who Had hypertension totalled 22.63 %. After being controlled by the covariate variables, the results showed that the obese respondents had 4.08 times higher odds of experiencing hypertension compared to the normal respondents (AOR= 4.08, 95% CI = 3.68-4.53, p-value = 0.000) and that the respondents who were overweight were 2.49 times likely to get hypertension compared to the respondents who were normal (AOR = 2.49, 95% CI = 2.32-2.67, p-value = 0.000). Meanwhile, the respondents with an underweight BMI were 0.58 times more likely to have hypertension compared to the respondents who were normal (AOR = 0.58, 95% CI = 0.52-0.65, p-value = 0.000). Conclusion: Individuals with a higher BMI will be more at risk of hypertension While physical activity is not related to hypertension. The government and health services need to increase the promotion of a healthy lifestyle, exceptionally robust diet programs, to encourage the population to maintain ideal body weight and to reduce the rate of hypertension.